Empathy in paedophilia and sexual offending against children: a longitudinal extension. Issue 2 (4th May 2022) - Schuler, Miriam; Mohnke, Sebastian; Amelung, Till; Dziobek, Isabel; Borchardt, Viola; Gerwinn, Hannah; Kärgel, Christian; Kneer, Jonas; Massau, Claudia; Pohl, Alexander; Weiß, Simone; Pieper, Susann; et al.
ABSTRACT: Deficits in cognitive empathy (CE) have been associated with a child sexual offense (CSO) history in paedophilia. However, these results have been obtained in cross-sectional comparison. There are no longitudinal studies yet. We performed a longitudinal study with a 3-year interval and investigated CE and emotional empathy (EE) using the Multifaceted Empathy Test (MET) and the Interpersonal Reactivity Index (IRI) in paedophilic men with a CSO history (P + CSO), paedophilic men without a CSO history (P-CSO), and non-offending teleiophilic male controls (TC). Results were stable and confirmed cross-sectional data with evidence for higher CE as measured by the MET in P-CSO compared to P + CSO. Evidence for more distress in social situations as measured by the IRI was found in P-CSO compared to TC, only. Our results highlight the importance of addressing multiple aspects of empathy in paedophilia and CSO and support the inclusion of CE training in the prevention of CSO.